Technology adoption on online learning during Covid-19 pandemic: implementation of technology acceptance model (TAM) - Tri Lestari Wahyuning Utami (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2021)
Individual behavior in technology adoption can be predicted by perception and belief. Implementing TAM, this study aims to analyze the behavioral teaching staff in using Google Apps for online learning. This study examined the effect of perceived usefulness, perceived ease of use, and user training and support on behavioral intention to use technology. We analyzed 108 samples using SPSS Process Model 4 and Model 15 to examine the mediation effect and moderated mediation effect. Our results show that perceived usefulness is confirmed to mediate the perceived ease of use behavioral intention to use technology. However, moderated mediation effect is not supported. This study contributed to advance the empirical evidence on the implications of TAM in analyzing technology adoption.